The Impact of Artificial Intelligence on Cybersecurity - Dindi, Ana; Qamili, Aurela; Karroçi, Enkela; Sheikhaleslami, Zahra (Karshi Multidisciplinary International Scientific Journal, 2024)
This article examines the role and applications of Artificial Intelligence (AI) in the field of cybersecurity, analyzing the opportunities and challenges it presents. Following a brief overview of AI development, the study focuses on the various methods used for protection against cyber threats, including the use of deep learning and machine learning algorithms to decipher threat models, analyze suspicious behaviors, and predict security incidents. The use of AI for malware protection, threat analysis, and automated incident response is crucial for enhancing the efficiency of defense against cyberattacks. However, the use of AI also presents challenges, including adversarial attacks and the difficulty in interpreting AI system decisions. The article also reviews the current trends and future perspectives of AI in cybersecurity, predicting an increased integration of AI into critical infrastructure and a rise in the autonomy of security systems. However, these developments require addressing challenges such as transparency and ethics in AI usage. This study concludes that AI has the potential to transform the field of cyber security but requires a cautious and supervised approach to maximize its benefits and address its risks.